SMEs’ Intention towards Sustainable Entrepreneurship - Majid, Izaidin Abdul; Aziz Latif,; Wei-Loon Koe, (European Journal of Multidisciplinary Studies, 2017)
Environmental degradation could be considered as one of the negative consequences of entrepreneurial activities. As such, entrepreneurs are urged to be proactive in resolving environmental problems through sustainable entrepreneurship. However, this new practice has not been fully accepted and exercised by many SMEs. Moreover, the studies pertaining to sustainable entrepreneurship are also very scarce in the literature. Therefore, this paper was conducted to investigate the contexts that directly and indirectly influence the SMEs owner-managers’ intention towards sustainable entrepreneurship. A model was developed based on Theory of Planned Behaviour and Entrepreneurial Event Model. This study surveyed 404 SMEs in Malaysia by using self-administered questionnaires. It found that owner-managers’ intention towards sustainable entrepreneurship was rather encouraging. In addition, factors such as positive sustainable value, favourable sustainable attitude, supporting social norm and sufficient governmental legislation directly increased the intention towards sustainable entrepreneurs. Moreover, those factors were also found to indirectly influence the intention through individual’s perception. As such, this paper pointed out some critical factors that should be emphasized in promoting and developing sustainable entrepreneurship. Some recommendations for future studies have also been given at the last part of this paper.
Keywords: Entrepreneurship, Intention, Perception, Small and medium enterprises (SMEs), Sustainability